Low cost miniaturized spectrometer for mid infrared sensing - Goh, Simon Chun Kiat (Nanyang Technological University, 2020)
Mid-infrared (MIR) spectroscopy is an attractive technology for the detection of molecules. It enables compounds to be identified rapidly. One main issue plaguing MIR sensing is that most equipment is bulky and is often laboratory-based. Hitherto, a miniaturized counterpart is facing several technological limitations: low power requirement, suitable optical filter for field use, uncooled detector operation at elevated temperature and the utilization of an appropriate packaging that confers physical and chemical protection. Because of the limitations, samples have to be brought back from the field for analysis. Often, it is challenging to survey samples with fast deterioration. To address the current limitations, a field operable miniaturized MIR spectrometer is proposed in this thesis. The scope of this thesis covers the fabrication and characterization of filters, mirrors and detectors. Specifically, as an optical filter is considered the heart of a spectrometer, it is given greater emphasis in this work. In particular, interferometric filters are discussed. Interferometric filters are arguably considered to be superior to other kinds of filters.